2021
DOI: 10.3390/su132212810
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Digestion of Lignocellulosic Waste Materials

Abstract: Nowadays, the climate mitigation policies of EU promote the energy production based on renewable resources. Anaerobic digestion (AD) constitutes a biochemical process that can convert lignocellulosic materials into biogas, used for chemical products isolation or energy production, in the form of electricity, heat or fuels. Such practices are accompanied by several economic, environmental and climatic benefits. The method of AD is an effective method of utilization of several different low-value and negative-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 86 publications
0
24
0
2
Order By: Relevance
“…AD processes take about three to six weeks, depending on the ease and degree of conversion of the input material into biogas and the technology used. Pretreatment, co-digestion, bioaugmentation, biohythane, temperature, organic loading rate and reactor design are some of the ways to increase biogas yield [89]. It has also been shown that pretreatment methods, such as substrate preparation, mechanical solubilisation in combination with low-temperature heat treatment, affect biogas yield in AD processes with wastewater sludge because of a higher ability to dissolve sludge and consequent acceleration of anaerobic digestion [90].…”
Section: Anaerobic Digestionmentioning
confidence: 99%
See 4 more Smart Citations
“…AD processes take about three to six weeks, depending on the ease and degree of conversion of the input material into biogas and the technology used. Pretreatment, co-digestion, bioaugmentation, biohythane, temperature, organic loading rate and reactor design are some of the ways to increase biogas yield [89]. It has also been shown that pretreatment methods, such as substrate preparation, mechanical solubilisation in combination with low-temperature heat treatment, affect biogas yield in AD processes with wastewater sludge because of a higher ability to dissolve sludge and consequent acceleration of anaerobic digestion [90].…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…With appropriate upgrades, biogas produced by the AD process can be used in many applications including systems with gas turbines and generators, internal combustion engines, production of heat for commercial and residential use and as a transport fuel at a very competitive price [89]. As mentioned previously, the two main components of biogas are methane CH 4 and carbon dioxide CO 2 , which are accompanied by other impurities such as nitrogen N 2 , oxygen O 2 , hydrogen H 2 , hydrogen sulphide H 2 S and ammonia NH 3 .…”
Section: Biogas Purification After Anaerobic Digestionmentioning
confidence: 99%
See 3 more Smart Citations